Evaluation of the safety of using harmonic scalpel during laparoscopic cholecystectomy in children: A preliminary report - Aboelela, Ahmed; Abouheba, Mohamed; Khairi, Ahmed; Kotb, Mostafa (Frontiers in Pediatrics, 2022)
Background & Objective: In spite of being one of the most common surgical procedures performed in adults, laparoscopic cholecystectomy (LC) is relatively uncommon in pediatric age group. Most surgeons prefer to dissect the cystic duct using a monopolar electrosurgical hook and occlude it with simple metal clips. Although the safety of using the ultrasonically-activated shears, e.g. Harmonic scalpel for dissection of the gallbladder is confirmed in many studies, its efficacy in the closure of the cystic artery and duct in adults is still debatable. Furthermore, very few reports studied its safety in children during LC. The aim of our work was to study the safety and efficacy of ultrasonic shears in controlling the cystic duct and artery during LC in children. Methods: A prospective study was conducted from May 2017 till April 2020, where all children having symptomatic gallbladder stone disease were included in the study. HS was used as a sole instrument in gallbladder dissection as well as in controlling cystic duct and artery. No metal clips or sutures were used throughout the procedure. Results: Forty-two children having symptomatic gallstone disease were included in the study. The main indication for LC was hemolytic anemia. Their age ranged from 3 to 13 years with a mean of 8.40 ± 3.25 years. All operations were completed laparoscopically, i.e. no conversion to open surgery was needed. The mean operative time was 40.0 ± 10.42 minutes. There was no intraoperative complications apart from gallbladder perforation in two cases during dissection from liver bed while the postoperative recovery was smooth in all patients. Patients started oral feeding after 11.30 ± 3.01 hours. The mean time for discharge was 25.47 ± 7.49 hours, ranged from 14 to 48 hours. Postoperative ultrasound for all cases showed no evidence of minor or major bile leaks or CBD injuries. Conclusion: This is the first report to evaluate the use of HS as a sole instrument during LC in pediatric age group. HS is a safe and efficient instrument that can be used alone in gallbladder dissection as well as controlling cystic duct and artery during LC in children.